BGer 6B 955/2022 vom 7. Oktober 2022 - Bundesgericht (2022)
Qualifizierter Raub (Art. 140 Ziff. 2 StGB); Tätlichkeiten (Art. 126 Abs. 1 StGB); Sachbeschädigung (Art. 144 Abs. 1 StGB); Willkür; Nichteintreten | Straftaten